Proceedings of the 9th International Conference on Computer Vision Theory and Applications 2014
DOI: 10.5220/0004687403090319
|View full text |Cite
|
Sign up to set email alerts
|

Fast Segmentation for Texture-based Cartography of whole Slide Images

Abstract: In recent years, new optical microscopes have been developed, providing very high spatial resolution images called Whole Slide Images (WSI). The fast and accurate display of such images for visual analysis by pathologists and the conventional automated analysis remain challenging, mainly due to the image size (sometimes billions of pixels) and the need to analyze certain image features at high resolution. To propose a decision support tool to help the pathologist interpret the information contained by the WSI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…On prostate specimens, Gorelick et al 18 achieved a class-averaged recall of 83.88% on eight tissue classes with an inference time of 2 min per 300 × 300 pixel sized patch. Apou et al 19 segmented breast cancer WSI into six classes and achieved a class-averaged sensitivity of 55.83% and a class-averaged specificity of 91.4%. The authors stated inference times of under 2 h per WSI.…”
Section: Applications In Digital Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…On prostate specimens, Gorelick et al 18 achieved a class-averaged recall of 83.88% on eight tissue classes with an inference time of 2 min per 300 × 300 pixel sized patch. Apou et al 19 segmented breast cancer WSI into six classes and achieved a class-averaged sensitivity of 55.83% and a class-averaged specificity of 91.4%. The authors stated inference times of under 2 h per WSI.…”
Section: Applications In Digital Pathologymentioning
confidence: 99%
“…26 The authors, however, merely performed a segmentation and did not infer labels for the computed superpixels. Other existing works manually extracted handcrafted superpixel feature vectors which were then classified using machine learning-based classifiers and thereby enabled a binary 22,27 or multiclass 12,18,19,28 semantic segmentation of medical images. On histological image data, this approach has facilitated the binary segmentation of WSIs in 20 to 45 min by Bejnordi et al 27 and up to 60 min by Balazsi et al 22 with good performance results indicated by Dice scores of 92.43% 27 and 69%, 22 respectively.…”
Section: Superpixel Classificationmentioning
confidence: 99%
“…In the field of texture-based segmenta-tion approaches Signolle et al 17 propose a method that incorporates several binary hidden wavelet domain Markov tree classifiers whose outputs are combined using majority voting. 19 . Due to the high variations in hardware resources and annotation quality, it is oftentimes difficult to compare image analysis algorithms in terms of classification accuracy and computational costs.…”
Section: Applications In Digital Pathologymentioning
confidence: 99%
“…superpixels, has proven advantageous. The potential of superpixel segmentation prior to classification has been shown for various applications including salient object detection 25 , road segmentation 26,27 and binary 22,28 or multi-class 18,19 semantic segmentation of medical images. The authors manually extract superpixel feature vectors which are provided as input to machine learning-based classifiers.…”
Section: Superpixel Classificationmentioning
confidence: 99%